PENINGKATAN MUTU PENDIDIKAN MADRASAH IBTIDAIYAH SWASTA MELALUI MANAJEMEN STRATEGIK - Widodo, Wahyudi; Azis Tata Pangarsa, Abd. (STAI Ma'had Aly Al-Hikam Malang, 2024)
Private Madrasah Ibtidaiyah education quality improvement through strategic management, is an effort to properly manage all madrasah resources based on internal and external analysis. The quality of private Madrasah Ibtidaiyah education as a basic level educational institution under the auspices of the Ministry of Religion, is currently required to adapt to the demands of society and technological developments that continue to change and develop.This study aims to analyze and find (1) the concept of improving the quality of private Madrasah Ibtidaiyah education through strategic management, (2) Models of improving the quality of private Madrasah Ibtidaiyah education through strategic management, (3) Supporting and inhibiting factors for improving the quality of private Madrasah Ibtidaiyah education through strategic management.